Indirect drive ignition at the National Ignition Facility. (27th October 2016) - Meezan, N B; Edwards, M J; Hurricane, O A; Patel, P K; Callahan, D A; Hsing, W W; Town, R P J; Albert, F; Amendt, P A; Berzak Hopkins, L F; Bradley, D K; Casey, D T; et al.
Abstract: This paper reviews scientific results from the pursuit of indirect drive ignition on the National Ignition Facility (NIF) and describes the program's forward looking research directions. In indirect drive on the NIF, laser beams heat an x-ray enclosure called a hohlraum that surrounds a spherical pellet. X-ray radiation ablates the surface of the pellet, imploding a thin shell of deuterium/tritium (DT) that must accelerate to high velocity ( v   >  350 km s −1 ) and compress by a factor of several thousand. Since 2009, substantial progress has been made in understanding the major challenges to ignition: Rayleigh Taylor (RT) instability seeded by target imperfections; and low-mode asymmetries in the hohlraum x-ray drive, exacerbated by laser-plasma instabilities (LPI). Requirements on velocity, symmetry, and compression have been demonstrated separately on the NIF but have not been achieved simultaneously. We now know that the RT instability, seeded mainly by the capsule support tent, severely degraded DT implosions from 2009–2012. Experiments using a 'high-foot' drive with demonstrated lower RT growth improved the thermonuclear yield by a factor of 10, resulting in yield amplification due to alpha particle heating by more than a factor of 2. However, large time dependent drive asymmetry in the LPI-dominated hohlraums remains unchanged, preventing further improvements. High fidelity 3D hydrodynamic calculations explain these results. Future research efforts focus on improved capsule mounting techniques and on hohlraums with little LPI and controllable symmetry. In parallel, we are pursuing improvements to the basic physics models used in the design codes through focused physics experiments.